John Drew interviewed by Selena Williams in the Descendents of First World War Soldier Settlers in N.S.W. oral history project - Drew, John, 1932-2014.; Williams, Selena (2011)
John Drew talks about his background and career as a surgeon; his training at Sydney University, Newcastle University and England; his family background including father's WWI service; their Soldier Settlement block near Leeton, the first irrigated block, with a second some distance away, the size of blocks; living conditions and problems dealt with; father taking up a third farm near Griffith (1937): markets and rice growing; his siblings; the countryside; father's farming background; repatriation benefits; farm work and entertainment; schooling and their transportation; Murrumbidgee Irrigation Area (MIA); domestic work, Coolgardie safe, kerosene refrigerator until the introduction electricity in the 1960s; childhood punishments at school and home; childhood activities, memories and responsibilities; their T Model Ford in the 1920s; their housing and accommodation; his father not attending Returned Services League or Anzac day marches; his father's gun collection; the eventual sale of the farm; family members WWII service; the deaths of his parents.
Recorded on 13 February 2011 in Huntleys Cove, N.S.W.
Mode of access: Online.
Timed summary (4 p.)
Keywords: Drew, John, -- 1932-2014 -- Interviews; Surgeons -- New South Wales -- Huntleys Cove -- Interviews; Soldier settlements -- New South Wales -- History; World War, 1914-1918 -- Veterans -- Australia; Veterans -- New South Wales